Correlation between periodontitis and chronic kidney disease in Korean adults - Seung Seok Han; Nara Shin; Su Mi Lee; Hajeong Lee; Dong Ki Kim; Yon Su Kim (Kidney Research and Clinical Practice, 2013)
Background: Periodontitis and chronic kidney disease (CKD) are important health issues; however, the association between periodontitis and CKD markers, especially in Korean adults, remains elusive. Methods: Data on 15,729 Korean adults were obtained from the Korean National Health and Nutritional Examination Surveys IV and V. The CKD markers included a decreased estimated glomerular filtration rate (eGFR;<60 mL/min/1.73 m2), proteinuria, and hematuria. Odds ratios (ORs) and 95% confidence intervals were measured using stepwise multivariate logistic regression analyses for CKD markers based on the presence of periodontitis. Results: Patients with periodontitis had greater unadjusted ORs for CKD markers compared to those without periodontitis, as follows: decreased eGFR, 4.07 (3.11–5.33); proteinuria, 2.12 (1.48–3.05); and hematuria, 1.25 (1.13–1.39, all P<0.001). Periodontitis was a significant predictor of decreased eGFR independent of all covariates [1.39 (1.03–1.89), P=0.034]. However, the effect of periodontitis on decreased eGFR seemed to be affected by hypertension and diabetes mellitus. Periodontitis was not an independent predictor of proteinuria; the significance disappeared after adjusting for hypertension and diabetes mellitus. Periodontitis was significantly correlated with hematuria, leading to similar ORs regardless of the adjustment for covariates [1.29 (1.15–1.46), P<0.001]. Conclusion: This study confirms the correlation between periodontitis and CKD markers, including decreased eGFR, proteinuria, and hematuria in Korean adults.